ECMM/ISHAM recommendations for clinical management of COVID‐19 associated mucormycosis in low‐ and middle‐income countries. Issue 9 (26th July 2021) - Rudramurthy, Shivaprakash M.; Hoenigl, Martin; Meis, Jacques F.; Cornely, Oliver A.; Muthu, Valliappan; Gangneux, Jean Pierre; Perfect, John; Chakrabarti, Arunaloke; ,
Abstract: Reports are increasing on the emergence of COVID‐19–associated mucormycosis (CAM) globally, driven particularly by low‐ and middle‐income countries. The recent unprecedented surge of CAM in India has drawn worldwide attention. More than 28, 252 mucormycosis cases are counted and India is the first country where mucormycosis has been declared a notifiable disease. However, misconception of management, diagnosing and treating this infection continue to occur. Thus, European Confederation of Medical Mycology (ECMM) and the International Society for Human and Animal Mycology (ISHAM) felt the need to address clinical management of CAM in low‐ and middle‐income countries. This article provides a comprehensive document to help clinicians in managing this infection. Uncontrolled diabetes mellitus and inappropriate (high dose or not indicated) corticosteroid use are the major predisposing factors for this surge. High counts of Mucorales spores in both the indoor and outdoor environments, and the immunosuppressive impact of COVID‐19 patients as well as immunotherapy are possible additional factors. Furthermore, a hyperglycaemic state leads to an increased expression of glucose regulated protein (GRP‐ 78) in endothelial cells that may help the entry of Mucorales into tissues. Rhino‐orbital mucormycosis is the most common presentation followed by pulmonary mucormycosis. Recommendations are focused on the early suspicion of the disease and confirmation of diagnosis. Regarding management, glycaemic control, elimination of corticosteroid therapy, extensive surgical debridement and antifungal therapy are the standards for proper care. Due to limited availability of amphotericin B formulations during the present epidemic, alternative antifungal therapies are also discussed.